CREATIVITY IN SYNCHRONOUS AND ASYNCHRONOUS LEARNING DURING THE COVID-19 PANDEMIC: A CASE STUDY - Muhammad Muzaini; Sri Rahayuningsih; Nasrun Nasrun; Muhammad Hasbi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
AbstractThe corona virus outbreak has forced all universities to conduct learning online using the internet. We have considered to develop students’ creativity through online learning. We therefore applied synchronous learning and asynchronous learning methods in the classroom and observed how these methods influenced students’ creativity. Purposive sampling technique was used to select one out of 40 students from the Department of Mathematics Education at STKIP YPUP to participate in this study. The subject was chosen because he had fulfilled the criteria of creativity. Data analysis was performed in several stages as follows: 1) analyzing the interview data and the learning videos; 2) performing data reduction by making abstractions; 3) organizing the data in units that were then categorized by coding; 4) checking the data validity by doing time triangulation; 5) analyzing interesting phenomena that are associated with the participant’s creativity. The results of the analysis showed that the subject’s creativity was demonstrated through cognitive flexibility and cognitive fluency, indicated by repeated or cyclic cognitive processes before the participant discovered the solution to the problem. It can be concluded that both synchronous and asynchronous learning methods can support the development of college students’ creativity during the covid-19 pandemic. Keywords: Covid-19 pandemic; creativity; synchronous and asynchronous learning. AbstrakWabah virus corona memaksa semua perguruan tinggi untuk melakukan pembelajaran secara online menggunakan internet. Kami telah mempertimbangkan untuk mengembangkan kreativitas siswa melalui pembelajaran online. Oleh karena itu, kami menerapkan pembelajaran synchronous dan metode pembelajaran asynchronous di kelas dan mengamati bagaimana metode ini mempengaruhi kreativitas siswa. Teknik purposive sampling digunakan untuk memilih satu dari 40 mahasiswa Jurusan Pendidikan Matematika STKIP YPUP untuk berpartisipasi dalam penelitian ini. Subjek dipilih karena telah memenuhi kriteria kreativitas. Analisis data dilakukan dalam beberapa tahapan sebagai berikut: 1) menganalisis data wawancara dan video pembelajaran; 2) melakukan reduksi data dengan membuat abstraksi; 3) mengorganisasikan data dalam satuan-satuan yang kemudian dikategorikan dengan pengkodean; 4) pengecekan keabsahan data dengan melakukan triangulasi waktu; 5) menganalisis fenomena menarik yang terkait dengan kreativitas peserta. Hasil analisis menunjukkan bahwa kreativitas subjek ditunjukkan melalui keluwesan kognitif dan kelancaran kognitif, yang ditunjukkan dengan proses kognitif berulang atau siklik sebelum partisipan menemukan solusi dari masalah. Disimpulkan bahwa metode pembelajaran synchronous dan asynchronous dapat mendukung pengembangan kreativitas mahasiswa selama masa pandemi covid-19. Kata Kunci: Pandemi Covid-19, Kreativitas, Pembelajaran Synchronous dan Asynchronous